(untitled) (Research, Society and Development, 2021)
In the present work analyzes the behavior of the three-phase induction machine with a wound rotor, which is widely used in the wind energy systems, operating as a generator under normal conditions and with unbalance voltage in the electrical system to which it is connected. For this, a mathematical model of the three-phase induction machine called “phase model” is adopted, in which coordinate or reference system transformations are not performed, in addition to taking into account the effects of magnetic saturation. The results from this model, which was implemented computationally, are compared with the results obtained in an experimental test platform. In both cases, the voltage and current curves were obtained, this data allowed, by means of comparison, to verify the satisfactory response of the mathematical model regarding the analyzed disturbance. From this, it was possible to conclude that the model is suitable for studies under normal operating conditions and with unbalance voltage.